Dynamic instability and migration modes of collective cells in channels. Issue 156 (26th July 2019) - Lin, Shao-Zhen; Bi, Dapeng; Li, Bo; Feng, Xi-Qiao
Abstract : Migrating cells constantly experience geometrical confinements in vivo, as exemplified by cancer invasion and embryo development. In this paper, we investigate how intrinsic cellular properties and extrinsic channel confinements jointly regulate the two-dimensional migratory dynamics of collective cells. We find that besides external confinement, active cell motility and cell crowdedness also shape the migration modes of collective cells. Furthermore, the effects of active cell motility, cell crowdedness and confinement size on collective cell migration can be integrated into a unified dimensionless parameter, defined as the cellular motility number (CMN), which mirrors the competition between active motile force and passive elastic restoring force of cells. A low CMN favours laminar-like cell flows, while a high CMN destabilizes cell motions, resulting in a series of mode transitions from a laminar phase to an ordered vortex chain, and further to a mesoscale turbulent phase. These findings not only explain recent experiments but also predict dynamic behaviours of cell collectives, such as the existence of an ordered vortex chain mode and the mode selection under non-straight confinements, which are experimentally testable across different epithelial cell lines.